Alphavirus Replicon Particle Vaccine Breaks B Cell Tolerance and Rapidly Induces IgG to Murine Hematolymphoid Tumor Associated Antigens - Su, Hsuan; Imai, Kazuhiro; Jia, Wei; Li, Zhiguo; DiCioccio, Rachel A.; Serody, Jonathan S.; Poe, Jonathan C.; Chen, Benny J.; Doan, Phuong L.; Sarantopoulos, Stefanie (Frontiers in Immunology, 2022)
De novo immune responses to myeloid and other blood-borne tumors are notably limited and ineffective, making our ability to promote immune responses with vaccines a major challenge. While focus has been largely on cytotoxic cell-mediated tumor eradication, B-cells and the antibodies they produce also have roles in anti-tumor responses. Indeed, therapeutic antibody-mediated tumor cell killing is routinely employed in patients with hematolymphoid cancers, but whether endogenous antibody responses can be incited to blood-born tumors remains poorly studied. A major limitation of immunoglobulin therapies is that cell surface expression of single tumor-associated antigen (TAA) targets is dynamic and varied, making promotion of polyclonal, endogenous B cell responses appealing. Since many TAAs are self-antigens, developing tumor vaccines that enable production of antibodies to non-polymorphic antigen targets remains a challenge. As B cell responses to RNA vaccines are known to occur, we employed the Viral Replicon Particles (VRP). VRP constructed to encode mouse FLT3 provoked a rapid IgG B-cell response to this self-antigen in leukemia and lymphoma mouse models. In addition, IgGs to other TAA were also produced. Our data suggest that vaccination with RNA viral particle vectors incites a loss of B-cell tolerance that enables production of anti-tumor antibodies. The work provides impetus to employ such strategies that lead to a break in B-cell tolerance and enable production of broadly reactive anti-TAA antibodies as potential future therapeutic agents for patients with hematolymphoid cancers.